Dual effects of Ru on the microstructural stability of a single crystal superalloy. (December 2021) - Sun, Jingxia; Liu, Jinlai; Li, Jinguo; Chen, Chao; Wang, Xinguang; Zhou, Yizhou; Sun, Xiaofeng
Abstract: Generally, Ru can inhibit the precipitation of TCP phase in most single crystal superalloys. However, in this study, we found that the inhibition is related to the location in the exposed specimen relative to the specimen surface: Ru inhibits the precipitation of TCP phase inside the sample but promotes it in the near surface region. The promotion of the TCP phase was proven to be related to oxidation. Microstructural analysis suggested that Ru degrades the oxidation resistance by disturbing the barrier property of the oxide scale. More Ni atoms are consumed due to the poor oxidation, resulting in the concentration gradient toward the interior of the samples, which changes the driving force of TCP precipitation. Graphical abstract: Image, graphical abstract